THE CHOICE OF WORDS IN POLITENESS OF REFUSAL AT PENELOPE MOVIE - Theresia, Melati; Autila, Rani (Universitas PGRI Sumatera Barat, 2019)
The aim of this research is describing and explaining the choice of words in politeness of refusal at Penelope movie. Research problem in this research is to find and analyze the choice of the words in poleteness of refusal at Penelope movie. There are three steps that are used in this research, they are collecting data, analyzing data and presenting the result of analyzing. In the collecting data, data were collected by observational method. This method was followed by non-participatory observational, recording and note taking technique. After collecting data, data were analyzed by using identity and distributional method. In addition, the results of data analysis were described by using formal and informal method. There are several the choice of word in politeness of refusal that were found in Penelope movie, such as sorry, please, thank, the modal of could, tag question, and negative interrogative sentence.